Implication of Trips Agreement In India For Economic Growth and Development: Balancing TRIPS Agreement with India's Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The Uruguay Round (1986 – 1994) was the turning point in the history ofIntellectual Property Rights. This round included the Agreement on IntellectualProperty Rights under which minimum uniform laws are to be carried out. TheAgreement on TRIPs came into force on 1 January 1995 and is to be implementedover a six-year period ending 31 December 2000 for developed countries and overa ten-year period ending 31 December 2004 for developing countries India hasalways remained committed to the WTO and in every sphere; it has stood by thosecommitments. Going by such commitments to the WTO, India has amended itsIntellectual Property Laws. Apart from meeting WTO obligations India has placedthis new regime due to its economic rational. It enables pioneering firms leadtime to recoup sunk cost on research and development. India is ranked as thefastest emerging economy and a major global player in the years to come. Thecountry has the largest scientific and technical human resources among top fivecountries in the world. India cannot afford to remain in isolation,disregarding the norms of international intellectual property rightsconvention. A careful consideration is equally essential in the future interestof macro-level development.